Hubungan Antara Status Gizi Dan Anemia denganSiklus Menstruasi Pada Remaja PutriDi SMA Batik 1 Surakarta - Noviandari, Indah; , Yuli Kusumawati, SKM. M.Kes (Epid); , Kusuma Estu Werdhani, SKM. M.Kes (2016)
Adolescence need adequate nutrition to face the changes they encountered, especially for adolescent girls associated with their reproductive system. Nutrition status influence reproductive system disorders and affecting on menstrual disorders. Other thing associated with menstrual disorders is anemia. The anemia causes hormonal system disorders that affect of menstrual disorders. The purpose of this research is to determine the relationship between nutritional status and anemia with the menstrual cycle on adolescent girls in SMA Batik 1 Surakarta. The method of this research is analytic observational with case control approach. The research population are girls at SMA Batik 1 Surakarta class of X, XI, and XII. Sample selection of the group case is using purposive sampling with 35 girls, and for control group is using simple random sampling of 35 girls. The statistical test is using chi square of SPSS 16 software. The result of this research showed that there are relation between nutritional status and menstrual cycles in adolescent girls in SMA Batik 1 Surakarta (p value = 0,036) and value of OR = 0,205 which mean normal nutritional status can prevent abnormal menstrual cycles. This research also showed that there are relation between anemia and menstrual cycles in adolescent girls in SMA Batik 1 Surakarta (p value = 0,000) and value of OR = 0,130 which mean not having anemia can prevent abnormal menstrual cycle.